2006
DOI: 10.1111/j.1600-0854.2006.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

PKCζ Is Required for Microtubule‐Based Motility of Vesicles Containing the ntcp Transporter

Abstract: Intracellular trafficking regulates the abundance and therefore activity of transporters present at the plasma membrane. The transporter, Na + -taurocholate co-transporting polypeptide (ntcp), is increased at the plasma membrane upon treatment of cells with cAMP, for which microtubules (MTs) are required and the PI3K pathway and PKCz have been implicated. However, trafficking of ntcp on MTs has not been demonstrated directly and the regulation and intracellular localization of ntcp is not well understood. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 57 publications
5
87
0
Order By: Relevance
“…It is of interest that in contrast to results with antibody to Kifc1, overall motility of vesicles is reduced after incubation with antibody to Kif5B. This is in agreement with results observed in several previous studies (Brady et al, 1990;Martin et al, 1999;Ligon et al, 2004;Theiss et al, 2005;Sarkar et al, 2006), suggesting that Kif5B activity is dominant over other motor activities (Sarkar et al, 2006). The finding that fission of vesicles is reduced when either Kifc1 or Kif5B activity is inhibited by antibody also suggests that the opposing forces resulting from activity of both motors are required for fission to occur.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…It is of interest that in contrast to results with antibody to Kifc1, overall motility of vesicles is reduced after incubation with antibody to Kif5B. This is in agreement with results observed in several previous studies (Brady et al, 1990;Martin et al, 1999;Ligon et al, 2004;Theiss et al, 2005;Sarkar et al, 2006), suggesting that Kif5B activity is dominant over other motor activities (Sarkar et al, 2006). The finding that fission of vesicles is reduced when either Kifc1 or Kif5B activity is inhibited by antibody also suggests that the opposing forces resulting from activity of both motors are required for fission to occur.…”
Section: Discussionsupporting
confidence: 80%
“…There was no evidence that the minus-end motility of these vesicles was due to substitution of dynein for Kifc2. Specifically, there was no inhibition of vesicle motility in the presence of 5 M vanadate (Figure 4), a treatment that inhibits dynein-mediated motility Sarkar et al, 2006), and there was no immunocolocalization of dynein with fluorescent ASOR-containing vesicles ( Figure 6A). Rather, as was found in studies of early endocytic vesicles from the rat, all motility in both wild-type and Kifc2 knockout mouse vesicles was inhibited by 1 mM AMP-PNP, an inhibitor of kinesin based motility (Vale et al, 1992;Bananis et al, 2000;Murray et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that transporter-containing intracellular vesicles can move along microtubules, powered by specific members of the molecular motor families, dynein and kinesin. 6,7 Although exact mechanisms still need to be discovered, the direction of movement can be regulated by the activity of specific vesicle-associated kinases and rabs. Interestingly, the proteins and motors associated with these vesicles appear to differ, depending on the transporter.…”
Section: Vesicle-based Trafficking: a Regulator Of Hepatocyte Transpomentioning
confidence: 99%